Van Tijm and Victor Gremonsky (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Van Tijm and Victor Gremonsky, in their comparative monetary work, have established two closely related, largely divergent approaches and research methods. The first to follow the approach of EvelFeilmann to look at international literary relations is a certain historical causation (historical theory). And the second approach to the theory of typology, influenced by the writings of A. Vesilowski monetary, influenced by German philosophers, starting in the second half of the eighteenth century. The term similarities and differences between literatures is presented as a result of similarity or difference in the movement of the development of societies and their conditions. However, their divergence in principle did not override their agreement on some partial issues and their divergence in other matters. This is what the research will try to look at, using extrapolation as a means to elucidate judgments, which were ignored by scholars and interested parties, in the hope of giving each person the right, both impartially and objectively, to adopt their texts.